1985
DOI: 10.1111/j.1399-6576.1985.tb02217.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Gastrointestinal Hormones in Cardiodepressive Shock

Abstract: In previous studies increased plasma levels of vasoactive intestinal polypeptide (VIP), somatostatin and pancreatic polypeptide (PP) were demonstrated in a porcine endotoxin shock model. Unchanged levels of gastric inhibitory polypeptide (GIP) and secretin point to a specific shock reaction of peptide release and not to a diffuse mucosal leakage. A porcine model of cardiodepressive shock was developed to enable discrimination to be made between a general low-flow state and endotoxin reaction. Infusion of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Thus, some authors of the 80's described high levels of VIP in patients and animals suffering endotoxemia, and showed a direct association with the disease degree, suggesting VIP as a cause of the disorder. Ten years later, some groups, in which we are included, suggested that the increased VIP levels in those disorders is not probably a cause but a consequence of the disease, and that VIP could be synthesized in response to the injury to try to regulate the deleterious effects of the excessive immune action [164][165][166][167][168][169][170][171]. It occurs the same in arthritis, where presence of VIP in synovial fluid is a manifestation of self regulation of the immune function in relation with disease [172].…”
Section: Vip and Pathologymentioning
confidence: 99%
“…Thus, some authors of the 80's described high levels of VIP in patients and animals suffering endotoxemia, and showed a direct association with the disease degree, suggesting VIP as a cause of the disorder. Ten years later, some groups, in which we are included, suggested that the increased VIP levels in those disorders is not probably a cause but a consequence of the disease, and that VIP could be synthesized in response to the injury to try to regulate the deleterious effects of the excessive immune action [164][165][166][167][168][169][170][171]. It occurs the same in arthritis, where presence of VIP in synovial fluid is a manifestation of self regulation of the immune function in relation with disease [172].…”
Section: Vip and Pathologymentioning
confidence: 99%